New Television Camera Systems Operation and Maintenance Contents for Training Radio, Television and Electronics Work Students in Nigeria - Uduafemhe, Maxwell E.; Raymond, Emmanuel (American Journal of Social Sciences and Humanities, 2019)
The study developed new television camera systems operation and maintenance contents for training Radio, Television and Electronics Work (RTVEW) students. Four stage of research and development (R&D) design was adopted. A total of 228 subject matter experts selected using; purposive and random sampling techniques. Data for the study were collected using a structured questionnaire that had a reliability coefficient of 0.83. The data were analysed using mean, standard deviation and t-test. The study revealed that: safety practices in cameramanship, studio and outdoor cable management techniques, camera control mode; manual, robotic and computerized, introduction to use of ICT products in filming, and introduction to internet, recording for video streaming, received a strong emphasis as the new cognitive contents for the operation and troubleshooting of television camera systems. The study also revealed that there was no significant difference between the mean responses of electrical/electronics industrial personnel and teachers on the new cognitive and psychomotor skills contents for the operation and maintenance of television camera systems. It was concluded that the skills acquired by RTVEW students would be boosted tremendously and their employability enhanced, if the training they receive incorporates the new contents for the operation and maintenance of television camera systems developed in this study. It was therefore, recommended that the latest facilities needed for the teaching and learning of skills in television cameras operation and maintenance should be provided by government and all stakeholders involved in the provision of Technical and Vocational Education and Training in Nigeria.